Leisure activities of selected low-income families in San Juan, Metro Manila - Tatad, Anna Marga V.; Dare, Evangeline M. (2010.)
ABSTRACT This study sought to provide an overview of the leisure activities pursued by low-income families. In particular, the research aimed to know the types of leisure activities low-income families engage in, their contentment with their present leisure practices, their preferred family leisure activities, the constraints they perceive in pursuing their leisure preferences and their view regarding the importance of family leisure activities. Self-report questionnaires distributed to parents using convenience sampling, were utilized to achieve the objectives of the study. The study was conducted in San Juan, Metro Manila because of the site's accessibility to the researcher. A total of 63 questionnaires qualified for the analysis. Results indicate that social bonding activities such as reunions and out-of-town vacations are the most popular type of family. This is followed by leisure activities involving visual, physical and mental stimulation like watching television, swimming and board games, respectively. The last type of family leisure involves personal development activities such as drawing, sing along, and going to church. Almost all of the respondents expressed contentment with their current leisure activities. On leisure preference, majority wished to have vacation, either travel abroad or locally. All of the parent-respondents were very positive with their views regarding the importance of spending leisure with the family. Its importance mainly lies on the fact that it fosters family solidarity by making parents closer to their children. Spending leisure with family also provide enjoyment in a way that keeps children away from developing unwanted vices.
Thesis (B.S. Home Economics)--University of the Philippines Diliman.
Keywords: Leisure--Philippines--San Juan; Family recreation--Philippines--San Juan